Environmental economic an elementary introduction - Kerry Turner, R | Pearce, David | Bateman, Ian (Estados Unidos | ESTADOS UNIDOS University Press / Baltimore, 1993)
The subject of environmental economics has became on important focus of debate around the world, with experts as well as ordinary citizens concluding that the environmental and the economy
Sin Especificar
Keywords: Economía ambiental